Isolation of Amylase Producing Bacteria from Soil, Identification by 16S rRNA Gene Sequencing and Characterization of Amylase - Islam, Tasnia; Choudury, Naiyyum; Hossain, M Mahboob; Khan, Trosporsha Tasnim (Bangladesh Journal of Microbiology, 2018)
The use of amylase enzyme has been extensive in different industrial sectors. Unfortunately, Bangladesh lacks any local production of amylase. This research was conducted to isolate and identify a local amylase producing bacteria from soil and characterize the crude amylase enzyme so that the information acquired can be used to eliminate the issue of amylase scarcity in Bangladeshi industries such as food, pharmaceuticals, garments, and textiles. Bacteria from soil were primarily screened on starch agar medium and out of 48 isolates, 17 were found to be amylase producers. The isolates were screened based on their clear zone ratio, enzyme activities and specific enzyme activities. The best isolate demonstrated an enzyme activity of 0.123 U/ml and specific enzyme activity of 0.173 U/mg. It was then identified by a combination of biochemical tests, morphological and microscopic characteristics along with 16S rRNA gene sequencing. A phylogenetic tree was also constructed which determined that this isolate was a strain of Bacillus cereus. Characterization of the crude amylase enzyme revealed that the optimum temperature of the enzyme was 75°C while the optimum pH was 7. Hence this amylase enzyme can be used in industrial processes that require high temperature and neutral pH conditions. Bangladesh J Microbiol, Volume 34 Number 1 June 2017, pp 1-6